Internationalism and the Labours of the Portuguese Colonial Empire (1945–1974) - Jerónimo, Miguel Bandeira (2016)
This article aims to analyse the relationship between the Portuguese Empire and two international institutions (the United Nations and the International Labour Organization) as concerns the organization and regulation of colonial labour after World War II. Stressing the historical ballast of this relationship, particularly during the inter-war years, the article points to the instances of debate and conflict as well as of cooperation developed by the several actors after 1945, in a context marked by mounting anti-colonial pressures and bipolar competition dynamics. Contrary to traditional accounts of an ‘isolated’ empire, this article sheds light on the need to include international and transnational scales of analysis in order to assess the actual trajectory of Portuguese late colonial State, marked by moments of reform as well as resistance to change.